1993
DOI: 10.1210/endo.133.4.8404617
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of four growth hormone/chorionic somatomammotropin-related complementary deoxyribonucleic acids differentially expressed during pregnancy in the rhesus monkey placenta.

Abstract: The close homology of the chorionic somatomammotropin (CS) genes with pituitary GH is unique to primates. Southern blots of rhesus genomic DNA probed with a human CS cDNA demonstrated that the rhesus gene family consists of at least five EcoRI fragments between 2.3-9.5 kilobases. Rhesus pituitary and placental cDNA libraries were screened for hCS-hybridizing clones. A pituitary GH cDNA was isolated that was 95% and 96% identical to human GH at the mRNA and protein levels, respectively. Thirteen placental clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Thus, clusters of PRL-like genes are found in rodents and ruminants (Forsyth & Wallis 2002) and a cluster of growth hormone-like genes is found in higher primates (Chen et al 1989, Golos et al 1993, Wallis et al 2001. Most other mammalian groups, including pig, rabbit and dog, do not appear to have such a cluster (Talamantes et al 1980, Forsyth & Wallis 2002, and in the case of dog this was confirmed by a BLAST search of the genome sequence.…”
Section: Biological Significance Of Episodic Evolution Of Prlr and Itmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, clusters of PRL-like genes are found in rodents and ruminants (Forsyth & Wallis 2002) and a cluster of growth hormone-like genes is found in higher primates (Chen et al 1989, Golos et al 1993, Wallis et al 2001. Most other mammalian groups, including pig, rabbit and dog, do not appear to have such a cluster (Talamantes et al 1980, Forsyth & Wallis 2002, and in the case of dog this was confirmed by a BLAST search of the genome sequence.…”
Section: Biological Significance Of Episodic Evolution Of Prlr and Itmentioning
confidence: 96%
“…Most other mammalian groups, including pig, rabbit and dog, do not appear to have such a cluster (Talamantes et al 1980, Forsyth & Wallis 2002, and in the case of dog this was confirmed by a BLAST search of the genome sequence. Placental lactogens appear to use the PRLR signaling pathway (Golos et al 1993, Soares et al 1998, Herman et al 2000, Biener et al 2003 like pituitary PRL. This might suggest that the episodic evolution observed for the PRLR reflects adaptation to the presence of multiple ligands.…”
Section: Biological Significance Of Episodic Evolution Of Prlr and Itmentioning
confidence: 99%
“…Most mammals and lower primates, such as the bush baby and the slow loris, have only a single copy of the GH gene in their genomes , Wallis et al 2001, while, as the result of a series of gene duplications, a cluster of GH-like genes has been observed in the marmoset, spider monkey, rhesus monkey and man (Chen et al 1989, Golos et al 1993, Wallis et al 2001, Wallis & Wallis 2002, Mendoza et al 2004. Humans have five GH-related genes, all located in chromosome 17q22-24 (George et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Functional members of the hGH/hCSH family have 191 amino-acid residues encoded by five exons, and the sequence similarity among members reaches more than 90% at the DNA level (Chen et al 1989). In the rhesus monkey, one pituitary-expressed GH gene and four placentaexpressed genes have been reported (Golos et al 1993). However, in the marmoset (a NWM), all the GH-like genes cluster together in the phylogenetic tree, and none cluster with any GH-like gene of human or rhesus monkey, indicating that the gene duplications that gave rise to the marmoset GH-like gene cluster were independent of those of man and rhesus monkey (Wallis & Wallis 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The rat gene differs from that of other mammals, including mouse, in that the second intron includes a repetitive sequence of approximately 500 bp (Barta et al 1981). Rats and mice, like most other non-primate mammals, contain a single GH gene, with no evidence for duplicate or multiple genes for GH-like proteins as is found in goat and sheep (Valinsky et al 1990) and higher primates (Chen et al 1989, Golos et al 1993. In man the GH-like proteins include placental lactogens, but in rodents and ruminants placental lactogens are prolactin-like (Wallis 1992).…”
Section: Introductionmentioning
confidence: 99%